The coloniser or the missionary? Identity crisis as a conflict in Biblical reception among the Agikuyu of Central Kenya - R. Muya (Acta Theologica)
The Bible was a new phenomenon among African cultures that treasure the oral traditions governing their moral and spiritual life. Many African communities were reluctant to welcome the biblical discourse because it not only disagreed with traditonal African religious practices, but it was also imposed on them by foreigners laden with negative political motives. This article examines the difficulty of distinguishing between the coloniser and the missionary as an initial conflict in biblical reception among the Agikuyu of Central Kenya. The article analyses how the missionaries inculcated the biblical message and how the Agikuyu gradually shifted from their initial belief that "there is no difference between a White coloniser and a White missionary" to a friendly relationship with missionaries and acceptance of Christianity. To explore these dynamics, the article employs witness accounts from African scholars, intertextual analysis of texts regarding Agikuyu because of the initial challenge of distinguishing British colonialists from missionaries. The results will contribute to understanding the dynamics of conflict in the reception of the biblical discourse and the reception of people by others in the world nowadays.